Reduction of CO2 emissions from road transport in cities : impact of dynamic route guidance system on greenhouse gas emission - Markiewicz, Michal (Springer Vieweg, 2016)
Michal Markiewicz presents the outcomes of his research regarding the influence of dynamic route guidance system on overall emission of carbon dioxide from road transport in rural areas. Sustainable transportation in smart cities is a big challenge of our time, but before electric vehicles replace vehicles that burn fossil fuels we have to think about traffic optimization methods that reduce the amount of greenhouse gas emissions.
Keywords: Intelligent transportation systems.; Urban transportation -- Environmental aspects.; Carbon dioxide mitigation.; Motor vehicles -- Pollution control devices.; elektronické knihy; electronic books